2020
DOI: 10.3389/fnagi.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid, Alzheimer-Related Brain Changes, and Cognitive Impairment

Abstract: Background: Despite known associations of lower serum uric acid (UA) with Alzheimer's disease (AD) dementia or AD-related cognitive impairment, little is known regarding the underlying patho-mechanisms. We aimed to examine the relationships of serum UA with in vivo AD pathologies including cerebral beta-amyloid (Aβ) and tau deposition, AD-signature region cerebral glucose metabolism (AD-CM), and white matter hyperintensities (WMH). We also investigated the association between serum UA and cognitive performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
3
22
2
Order By: Relevance
“…The different results to our study may partially be explained by the differences in the study populations (i.e., ethnicity, selection, age range); analysis (no sex‐stratified analysis in Kim et al. 24 ); and the methods used for the detection of amyloid deposition, positron emission tomography (PET) scan in Kim et al. 24 and CSF markers by us, which may differ with regard to the timing, sensitivity, and specificity for the detection of Aβ deposition.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The different results to our study may partially be explained by the differences in the study populations (i.e., ethnicity, selection, age range); analysis (no sex‐stratified analysis in Kim et al. 24 ); and the methods used for the detection of amyloid deposition, positron emission tomography (PET) scan in Kim et al. 24 and CSF markers by us, which may differ with regard to the timing, sensitivity, and specificity for the detection of Aβ deposition.…”
Section: Discussioncontrasting
confidence: 80%
“… 24 ); and the methods used for the detection of amyloid deposition, positron emission tomography (PET) scan in Kim et al. 24 and CSF markers by us, which may differ with regard to the timing, sensitivity, and specificity for the detection of Aβ deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AD-CM was the link of UA and cognitive measure scores. A decreased level of SUA was relevant to AD-related cerebral hypometabolism [42]. In previous studies, few studies had included multimodal brain imaging to observe the relationship between uric acid and brain changes.…”
Section: Level Of Sua Was Relevant To Thementioning
confidence: 99%
“…Therefore, the two aspects interacted with each other and accelerated the development of AD. Additionally, it has been demonstrated that increasing antioxidative potential correlated with a reduction of white matter injury [42].…”
Section: Ua Was Related To Ad Through Multiple Mechanismsmentioning
confidence: 99%